Silences in the boom: coal seam gas, neoliberalizing discourse, and the future of regional Australia - Alexandra Mercer (Journal of Political Ecology, 2014)
In high-stakes resource use struggles currently playing out across the world, different beliefs about economics and "growth-first" regional development underpin decisions and dynamics that have far-reaching consequences. Neoliberalizing political economies rely on the maintenance of particular beliefs associated with these themes, and work to delegitimize and silence alternatives. Thus understanding the beliefs of actors concerning these themes, especially with respect to neoliberal ideas, is key to understanding these sociopolitical struggles. This article uses a combination of literature review, critical discourse analysis and selected fieldwork data to explore the recent debate about coal seam gas (CSG) in Eastern Australia. In particular, it examines the ideas that underlie texts produced by CSG production companies, the Queensland Government, and Lock the Gate (a key group opposed to rapid CSG industry expansion). The analysis indicates that with respect to the above themes, Lock the Gate expresses their opposition to CSG through perspectives that mostly depart from those with a key role in maintaining neoliberalizing political economies. In contrast, the Queensland government and CSG companies, despite each encompassing significant internal diversity, have expressed relatively similar and consistent positions, aligned with neoliberalizing ideas. The article problematizes descriptions of the state government as a neutral arbitrator that can restore balance between the beliefs of gas companies and groups like Lock the Gate, and advances consideration of deeper differences.